HRCT PULMONARY FEATURES OF ILD PATIENTS ASSOCIATED WITH CONNECTIVE TISSUE DISEASES- AN OVERVIEW - Dimitrijevikj, Kristina (Journal of Morphological Sciences; Vol 8 No 1 (2025): JMS, 2025)
Connective tissue diseases (CTDs) include a spectrum of disorders that affect the connective tissue of the human body, They include autoimmune disorders such as rheumatoid arthritis (RA), systemic lupus erythematous (SLE), scleroderma, polymyositis/dermatomyositis and mixed connective tissue disease (MCTD) characterized by immune-mediated chronic inflammation and the development of fibrosis.  In this review article we will present cases of patients diagnosed with connective tissue disorders who developed interstitial lung diseases. Rheumatoid arthritis RA-ILD in our case is presented with usual interstitial pneumonia pattern (UIP) and NSIP pattern, SLE, scleroderma, dermatomyositis, MCTD are more common presented with nonspecific interstitial pneumonia pattern (NSIP). Sjogren syndrome in our case is presented on HRCT as organizing pneumonia (OP), but we can not exclude for sure primary postinfectious cause. Lymphocytic interstitial pneumonia pattern (LIP) is also presented in one patient diagnosed with Sjogren syndrome. HRCT of the lungs is a key component in the multidisciplinary approach to the diagnosis of connective tissue diseases associated with interstitial lung disease. The evaluation of radiological lung changes in correlation with clinical data not only leads to a correct diagnosis in many cases, but in this context plays an important role and helps in determining the prognosis, monitoring the effectiveness of treatment, detecting disease progression or complications, and evaluating patients with worsening or acute symptoms.   Key words: Connective tissue diseases, ILD, HRCT, lungs, UIP, NSIP, OP, LIP.